2005
DOI: 10.1158/1535-7163.mct-05-0222
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of DNA damage–induced apoptosis by the proteasome inhibitor PS-341 is p53 dependent and involves target proteins 14-3-3σ and survivin

Abstract: Proteasome inhibition following DNA damage results in the synergistic induction of apoptosis via a nuclear factor-KBindependent mechanism. In this study, we identify the role of p53 in mediating apoptosis by the sequence-specific treatment involving the DNA-damaging, topoisomerase I -targeting drug SN-38 followed by the proteasome inhibitor PS-341 (SN-38!PS-341). The p53-dependent sensitization of DNA damage -induced apoptosis by PS-341 is accompanied by persistent inhibition of proteasome activity and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
(36 reference statements)
1
26
1
Order By: Relevance
“…These results are in agreement with previous findings in myeloid leukemia cells, melanoma, mantle lymphoma, and myeloma cells in which bortezomib activity occurs in a p53-independent manner (36)(37)(38). It has however, been reported that in some cases, bortezomib activity could occur in a p53-dependent manner, for example, in response to DNA damage (39).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with previous findings in myeloid leukemia cells, melanoma, mantle lymphoma, and myeloma cells in which bortezomib activity occurs in a p53-independent manner (36)(37)(38). It has however, been reported that in some cases, bortezomib activity could occur in a p53-dependent manner, for example, in response to DNA damage (39).…”
Section: Discussionsupporting
confidence: 93%
“…TIAM1, a guanine nucleotide exchange factor, has been shown to enhance resistance to anoikis (apoptosis due to detachment) in SW480 colon cancer cells and thereby promotes cell survival and tumor metastasis (Minard et al, 2006). BIRC5 (commonly known as survivin) is a typical anti-apoptotic factor in colon tissues, and its increased expression positively correlates with tumor survival (Vaziri et al, 2005;Hernandez et al, 2011). Given that cells require more protection against DNA-damage-induced apoptosis during the S-G2 phase (Bartek et al, 2004;Huang et al, 2005), promoting the expression of anti-apoptotic genes during this period might present a fundamental function of Wnt-b-catenin signaling.…”
Section: S-g2-specific Functions Of the Wnt-b-catenin Signalingmentioning
confidence: 99%
“…Inhibition of the proteasome can also raise cellular p53 levels, again promoting shut-down of cell division. This is because the E3 ubiquitin ligase MDM2 targets p53 for degradation by the 26S proteasome (157).…”
Section: The Proteasome and Oxidative Stressmentioning
confidence: 99%